Improved power conversion efficiency in Perovskite solar cell using silver nanoparticles modified photoanode. Issue 1 (March 2020) - Eli, D; Onimisi, MY; Garba, S; Gyuk, PM; Jamila, T; Boduku, HP
Abstract: Metal nanoparticles have demonstrated outstanding properties in photovoltaic devices through introducing localized surface plasmon effects. The performance of Perovskite solar cell (PSC) by incorporating Ag@P4 VP NPs was investigated systematically. The plasmonic enhancement effects are explored based on the combination of UV-visible absorption spectroscopy and Scanning Electron Microscope (SEM). The performance, especially the short circuit current density (Jsc), and open circuit voltage (Voc) of the PSC containing Ag@P4 VP NPs was significantly affected. The power conversion efficiency (PCE), Jsc and Vocof the reference device shows a value of 3.80 %, 11.04 mAcm −2 and 0.85 V. Upon introducing AgNPs@P4 VP, a PCE of 5.69 %, Jsc of 12.61 mAcm −2 and Voc of 0.88 V were recorded, which improved the PCE ∼ 39.4 % over that of the standard device. The improvement is attributed to an increase in photocurrent density due to enhanced light harvesting by silver nanoparticles.